The mlpt/Ubr3/Svb module comprises an ancient developmental switch for embryonic patterning. - Ray, S.; Rosenberg, M.I.; Chanut-Delalande, H.; Decaras, A.; Schwertner, B.; Toubiana, W.; Auman, T.; Schnellhammer, I.; Teuscher, M.; Valenti, P.; Khila, A.; Klingler, M.; et al. (eLife, 2019)
Small open reading frames (smORFs) encoding 'micropeptides' exhibit remarkable evolutionary complexity. Conserved peptides encoded by mille-pattes (mlpt)/polished rice (pri)/tarsal less (tal) are essential for embryo segmentation in Tribolium but, in Drosophila, function in terminal epidermal differentiation and patterning of adult legs. Here, we show that a molecular complex identified in Drosophila epidermal differentiation, comprising Mlpt peptides, ubiquitin-ligase Ubr3 and transcription factor Shavenbaby (Svb), represents an ancient developmental module required for early insect embryo patterning. We find that loss of segmentation function for this module in flies evolved concomitantly with restriction of Svb expression in early Drosophila embryos. Consistent with this observation, artificially restoring early Svb expression in flies causes segmentation defects that depend on mlpt function, demonstrating enduring potency of an ancestral developmental switch despite evolving embryonic patterning modes. These results highlight the evolutionary plasticity of conserved molecular complexes under the constraints of essential genetic networks.